Baltic Salmon and Trout Assessment Working Group (WGBAST) - Bajinskis, Jani; Bernas, Rafal; Dahlgren, Elin; Dannewitz, Johan; Debowski, Piotr; Ek, Caroline; Ivanauskas, Edgaras; Kagervall, Anders; Karlsson, Konrad; Kesler, Martin; Kontautas, Antanas; Leinonen, Tuomas; et al. (ICES, 2024)
The Baltic Salmon and Trout Assessment Working Group (WGBAST) was mandated to assess the status of salmon in Gulf of Bothnia and Main Basin (Subdivisions 22–31), Gulf of Finland (Subdivision 32) and sea trout in Subdivisions 22–32, and to propose consequent management advice for fisheries in 2025. Salmon in Subdivision 22–31 were assessed using Bayesian methodology with a stock projection model (data up to 2023) for evaluating effects of different catch options on the wild river stocks. Section 2 of the report covers catches and other data on salmon in the sea and summarizes information affecting the fisheries and management of salmon. Section 3 reviews data from salmon spawning rivers, stocking statistics and health issues. Status of salmon stocks in the Baltic Sea is evaluated in Section 4. The same section also covers methodological issues of assessment as well as sampling protocols and data needs for assessment. Section 5 presents data and assessed stock status for sea trout. · Total salmon catches have decreased continuously since the 1990s. In 2022 and 2023, commercial salmon fishing has been restricted to Gulf of Bothnia, Åland Sea, and Gulf of Finland. · In Baltic Main Basin, only recreational salmon trolling is allowed and daily bag limit is one adipose fin clipped salmon per day. · The production of salmon smolts gradually increased from early 1990s to early 2010s in Gulf of Bothnia and Gulf of Finland. The production has since then levelled out. Long-term trends for smolt production in Main Basin rivers have remained relatively stable, but with large interannual fluctuations. · The current (2023) total wild production in all Baltic Sea rivers is close to 3 million smolts, corresponding to about 85% of overall potential smolt production capacity. In addition, about 3.6 million hatchery-reared smolts were released into the Baltic Sea in 2023. · Survival of wild post-smolts has varied between 10% and 20% since the mid-2000s, but declined to lower levels in 2020 and 2021, the 2021 value being the lowest ...